Supply chain risk management how to design and manage resilient supply chains - Manners-Bell, John (Kogan Page, 2024)
"Navigate a continually evolving global risk landscape and react to new logistical challenges effectively with this vital guide on supply chain risk.Implementing robust supply chain strategies has never been so essential in today's everchanging world. From geo-political risks to the continued effects of global crises, Supply Chain Risk Management is an essential resource for those wanting to mitigate risk and ensure supply chain resilience. Offering crucial insight from a management perspective, this updated 4th edition offers new guidance on the effects of the Covid-19 pandemic, supply-chain bottlenecks and evolving geo-political risks.With new global case studies including disruption to the supply chain due to the Suez Canal blockage and global tensions like the US-China trade war, this edition explores a variety of real-world risks. This book details ongoing threats like climate change, corruption and technological risks while providing crucial detail on how to implement robust systems and safeguard supply chain operations. Combining theoretical and practical learning, Supply Chain Risk Management is essential for those needing to understand risk and how it can be approached
Literaturverzeichnis Seite 399-415
Keywords: Supply Chain Management; Risikomanagement; Business logistics; Materials management; Risk management; Logistique (Organisation); Gestion de l'approvisionnement; Gestion du risque; risk management